Synthetic and bioactivity studies of antiplasmodial and antibacterial marine natural products,Synthetic and bioactivity studies of antiplasmodial and anti-bacterial marine natural products - Young, Ryan Mark (Rhodes University, Faculty of Science, Department of Chemistry, 2012)
This thesis is divided into two parts, assessing marine and synthetic compounds active firstly against Plasmodium falciparum (Chapter 3 and 4) and secondly active against methicillin resistant Staphylococcus aureus (MRSA, Chapter 5). In Chapter 3 the synthesis of nine new tricyclic podocarpanes (3.203-3.207 and 3.209-3.212) from the diterpene (+)-manool is described. Initial SAR study of synthetic podocarpanes concluded that the most active compound was a C-13 phenyl substituted podocarpane (3.204, IC₅₀ 6.6 μM). By preparing analogues with varying halogenated substituents on the phenyl ring (3.209-3.212) the antiplasmodial activity was improved (IC₅₀ 1.4 μM), while simultaneously decreasing the haemolysis previously reported for this class of compounds. Inspired by the antiplasmodial activity of Wright and Wattanapiromsakul's tricycle marine isonitriles (2.16-2.21 and 2.24-2.27) an unsuccessfully attempt was made to convert tertiary alcohol moieties to isonitrile functionalities in compounds 3.188, 3.204-3.207 and 3.209-3.212. Over a decade ago Wright et al. proposed a putative antiplasmodial mechanism of action for marine isonitriles (2.4, 2.9, 2.15, 2.19 and 2.35) and isothiocyanate (2.34) which involved interference in haem detoxification by P. falciparum thus inhibiting the growth of the parasite. In Chapter 4 we describe how we successfully managed to scale down Egan's β-haematin inhibition assay for the analyses of small quantities of marine natural products as potential β-haematin inhibitors. Our modified assay revealed that the most active antiplasmodial marine isonitrile 2.9 (IC₅₀ 13 nM) showed total β-haematin inhibition while 2.15 (IC₅₀ 81 nM) and 2.19 (IC₅₀ 31 nM) showed partial inhibition at three equivalents relative to haem. Using contempary molecular modelling techniques the charge on the isonitrile functionality was more accurately describe and the modified charge data sets was used to explore docking of marine isonitriles to haem using AutoDock. In Chapter 5 we describe how a lead South African marine bisindole MRSA pyruvate kinase inhibitor (5.8) was discovered in collaboration with colleagues at the University of British Columbia (UBC) and how this discovery inspired us to design a synthetic route to the dibrominated bisindole, isobromotopsentin (5.20) in an attempt to increase the bioactivity displayed by 5.8. We devised a fast and high yielding synthetic route using microwave assited organic synthesis. We first tested this synthesis using simple aryl glyoxals (5.27-5.32) as precursors to synthesize biphenylimidazoles (5.21-5.26), which later allowed us to synthesize the ascidian natural product 5.111. This method was sucessfully extended to the synthesis of deoxytopsentin (5.33) from an N-Boc protected indole methyl ketone (5.89). We subsequently were able to effectively remove the carbamate protection via thermal decomposition by heating the protected bisindole imidazole (5.90) in a microwave reactor for 5 min under argon. The synthesis of 5.20 resulted in an inseparable mixture of monoprotected and totally deprotected topsentin products, and due to time constraints we were not able to optimise this synthesis. Nonetheless our synthesis of the marine natural product 5.33 which was faster and higher yielding than previously reported routes could be extended to the synthesis of other topsentin bisindoles (5.138-5.140). Work towards this goal continues in our laboratory.
Keywords: Antibacterial agents; Marine natural products; Marine pharmacology; Plasmodium falciparum; Staphylococcus aureus; Isocyanides Imidazoles